BIOSTRATIGRAPHY ANALYSIS OF BARBATOS-1 EXPLORATION WELL IN TOMORI BLOCK, BANGGAI BASIN, EAST ARM OF SULAWESI - Anis Kurniasih; Ennur Kusumawijaya; Ferdy Ferdy; Fahrudin Fahrudin; Reddy Setyawan (Indonesian Institute of Sciences, 2021)
A biostratigraphic analysis was carried out on 60 samples taken from the Barbatos-1 Well, located within the Tomori Block, Banggai Tertiary Basin, East Arm of Sulawesi. The Barbatos-1 well was selected for this study because it is composed of rock sequences which are the main reservoir in the Tomori Block. Biostratigraphic analysis was conducted to determine the relative age and depositional environment of the sample. The age of the sample is determined based on the interval zone. The depositional environment is estimated basedon the ratio of plankton (P/B ratio) and fossil facies. The results revealed that the rock formations studied were deposited in the Miocene to Holocene age. The lowest layer is the Orbulina bilobata-Zone which was deposited at N10 – N12 (lower Middle Miocene) in the bathyal environment. The layer above is a biozonation of Globorotalia menardii, deposited at N12 – N14 (upper Middle Miocene) in a neritic environment. The next layer is the biozonation of Sphaeroidinella subdehiscens – Globigerina praebulloides which wasdeposited at N14 – N17 (Middle Miocene – Late Miocene) in the bathyal environment. The topmost layer is the biozonation of Orbulina universa – Globigerinoides immaturus which was deposited at N17 –N23 or Pliocene – Holocene in the bathyal environment. In the top two layers, there are fossil fragments that come from older rock layers (Early Tertiary).